Effects Of Voluntary Disclosure Of The Schedule Of Manufacturing Cost On Analysts’ Earnings Forecasts: Evidence From Korea - Oh, Hyunmin; Park, Sambock; Jeon, Heungjoo (Journal of Applied Business Research, 2017)
We provide the effects of voluntary disclosure of the schedule of manufacturing cost on analysts’ earnings forecasts. We set up and analyze the disclosure of the schedule of manufacturing cost as a proxy for voluntary disclosure. Specifically, we examine the associations between voluntary disclosure of it and the accuracy of analysts’ earnings forecasts and bias in earnings forecasts. The results of our study are as follows. First, the relationship between voluntary disclosure of the schedule of manufacturing cost and the accuracy of analysts’ earnings forecasts is significant in the positive (+) direction. This means that the accuracy of analysts’ earnings forecasts is higher in the case of the firms that voluntarily disclosed the schedule of manufacturing cost, as compared to other firms. Second, the relationship between voluntary disclosure of the schedule of manufacturing cost and analysts’ bias in earnings forecasts is significant in the negative (-) direction. This means that analysts underestimate earnings in the case of the firms that voluntarily disclose the schedule of manufacturing cost, as compared to other firms. Since the schedule of manufacturing cost is still an interesting item and useful information in the capital market, the results of our study provide important implications not only to managers, but also to investors and supervisory authority. Limitations of our study include the fact that not all diverse variables that affect voluntary disclosure and analysts’ forecasts are considered.